Remanufacturing end‐of‐life silicon photovoltaics: Feasibility and viability analysis. (3rd December 2020) - Deng, Rong; Chang, Nathan; Lunardi, Marina Monteiro; Dias, Pablo; Bilbao, Jose; Ji, Jingjia; Chong, Chee Mun
Abstract: With the rapid deployment of silicon solar photovoltaic (PV) technologies around the world, the volume of end‐of‐life (EoL) PV modules will increase exponentially in the next decade. Different EoL management strategies are being explored in the industrial and academic fields, such as recycling, remanufacturing and reusing. In this study, we used a Monte Carlo uncertainty model to identify the potential economic benefits of closed‐loop recycling of EoL PV modules when recycled silicon is integrated into different stages of the PV supply chain. Circular use of high‐purity silicon and intact silicon wafers from EoL PV modules can be economically feasible in reducing 20% of the manufacturing cost of the second‐life modules, even with some efficiency reductions. Even though the price of new PV modules is decreasing rapidly (making PV modules less attractive from a recycling perspective), circular use of material from EoL modules in second‐life production was found to have promising long‐term environmental and economic benefits. The cost–efficiency trade‐off is shown to provide cost targets for new PV recycling technologies. Abstract : End‐of‐life photovoltaic modules can be recycled to provide materials to the supply chain to manufacture 'second‐life' modules. We analysed three silicon recycling options to identify targets for recycling costs and quality so that such remanufactured modules can be economically viable. We provided a case study to demonstrate that these targets are achievable. With further cost reduction of recycling processing in the future, closed‐loop recycling will create a significant value for the photovoltaic industry.